A Comparative Analysis of the Scope of Immaterial Damage in Indonesia and the Netherlands - Arnapi, Muhammad Almer Putera (Universitas Airlangga, 2025)
The determination of immaterial damage often hinges on judicial discretion, a practice that raises important questions of fairness and consistency across jurisdictions. This paper examines how such discretion operates in Indonesia and the Netherlands. Using a normative legal method and comparative analysis, the study evaluates statutory provisions and judicial practice. Dutch law recognizes three grounds for compensation in cases of immaterial damage. In practice, however, judges apply a two-tiered test: first, to determine whether the victim’s situation falls within the recognized grounds, and second, to assess whether the suffering is of sufficient severity. In contrast, Indonesian law provides no explicit rules on immaterial damage, leaving judges with broad discretion but without official guidelines. The reliance on discretion in both jurisdictions highlights risks of subjectivity and underscores the need for clearer standards to ensure fairness and legal certainty in compensation.